Study guides

Q: What is p if 6p plus 3 equals 8p plus 6?

Write your answer...

Submit

Related questions

algebra8p +4 = 10 +6p+8p - 6p = +10 - 42p = 6p = 3

9p - 5

Assuming you mean 7 multiplied by just 2p and assuming that p is a variable then p is calculated by: (7 * 2p) + 3 - 8 = 6p + 29 14p - 5 = 6p + 29 14p - 6p = 29 + 5 8p = 34 p = 4.25

-8p + 3 = -29 8p - 3 = 29 8p = 29 + 3 8p = 32 p = 32/8 p = 4

17 + 6p = 9 6p = -8 p = -8/6 p = -4/3

3p + 6p = (3 + 6)p = 9p

5p-14 = 8p +4 take the 14 to the other side and the 8p to the other side so 5p-8p = 4 +14 -3p = 18 p = -18/3

2

4p+3 = -6p-5 4p+6p = -5-3 10p = -8 p = -0.8 Substituting the value of p into the original equation gives you: -1/5 = -1/5

9p+1 = 1p+3 Take away 1p from each side: 8p+1=3 Take away 1 from each side: 8p = 2 Divide both sides by 8: p = 2/8 = 1/4

8p - 3 = 13 add 3 to both sides 8p = 16 divide by 8 to both sides p = 2

8p+2=4p-10 8p-4p=-2-10 4p=-12 p=-12/4 =-3

-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r

If we have 6p+3 The common factor to both 6p and 3 is 3. If we take this out the front of brackets we get 3(2p+1)

5p+18 = 8p Subtract 5p from both sides: 18 = 3p Divide both sides by 3: 6 = p or as p = 6

No.

42

3 plus 1 plus 4 equals 8

4 plus 3 equals 7

67 plus 3 equals 70.

89

12

-9 plus 6 equals -3.

First get all the p variables on one side of the equation by subtracting 6p from both sides. Giving you 3p + 14 = 23 Now subtract 14 from both sides. 3p = 9 Finally divide both sides by 3. p = 3

4+1=5. Plus 4 equals 9. Plus 77685769844446473 equals 77685769844446482. Plus 3 equals 77685769844446485. Plus 8 equals 77685769844446493. Plus 1 equals 77685769844446494. Plus 9870998342523322424 equals 1064785604097768918. Plus 4 equals 1064785604097768922.